Pengaruh Penggunaan E-Jobsheet untuk Peningkatan Kompetensi pada Mata Kuliah Praktek Pembuatan Busana Wanita dan Anak Wanita - Wahyu Eka Priana Sukmawaty; Jumariah, Jumariah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyse the effect of using e-jobsheets on improving student competence in women's and girls' clothing design courses. This study uses a quantitative approach with a quasi-experimental design. The research population comprises all students enrolled in women's and girls' clothing design courses within a single fashion design study program. The sample was selected using purposive sampling, consisting of two groups: the experimental group (using e-jobsheets) and the control group (using conventional jobsheets). The research procedure consisted of three stages: pre-test, treatment, and post-test. Data collection was carried out using a validated competency test instrument. The primary research instrument was a sewing competency test consisting of multiple-choice questions and practical garment-making tasks. The validity and reliability of the instrument were tested before use to ensure objective and reliable results. The pre-test and post-test data were statistically analysed using an independent sample t-test to determine the difference in competency improvement between the experimental and control groups. This study showed that the use of e-jobsheets can improve student competency in women's and girls' clothing design courses. Students who used e-jobsheets showed an increase in their ability to make clothing independently and in a structured manner. Additionally, students were also better able to identify and address errors in the clothing-making process.